[TEX]P=\frac{2n+9}{n+2}+\frac{4n+17}{n+2}+\frac{4n+15} {n+2}[/TEX]
Theo mình nghĩ thì thế này:
[TEX]P=\frac{2n+9}{n+2}+\frac{4n+17}{n+2}+\frac{4n+15} {n+2}[/TEX]
[TEX]P=\frac{2n+9+4n+17+4n+15}{n+2}[/TEX]
[TEX]P=\frac{2n+4n+4n+9+17+15}{n+2}[/TEX]
[TEX]P=\frac{n(2+4+4)+41}{n+2}[/TEX]
[TEX]P=\frac{n10+41}{n+2}[/TEX]
[TEX]\Rightarrow n10+41 \vdots[/TEX] Ư(1)
[TEX]\Rightarrow n+2 \vdots[/TEX] Ư(1)
[TEX]\Rightarrow (n10+41) - (n+2) \vdots[/TEX] Ư(1)
[TEX]\Rightarrow (n10+41)-(n1+2) \vdots[/TEX] Ư(1)
[TEX]\Rightarrow n11+43 \vdots[/TEX] Ư(1)
Ư(1)={-1;1}
Nếu [TEX]n11+43=1[/TEX] thì [TEX]n=(1-43):11 \Rightarrow n= \frac{-42}{11}[/TEX] => Loại bỏ, vì đây không thuộc Z
Nếu [TEX]n11+43=(-1)[/TEX] thì [TEX] n=[(-1)-43]:11 \Rightarrow n= (-4)[/TEX]
\Rightarrow Nếu n ∈ { -4 } thì [TEX]P=\frac{2n+9}{n+2}+\frac{4n+17}{n+2}+\frac{4n+15} {n+2}[/TEX] tối giản